2012
DOI: 10.1111/j.1439-0531.2012.02132.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Post‐Thaw Sperm DNA Integrity and Non‐Return Rate Among Norwegian Cross‐Bred Rams

Abstract: With the aim of investigating the relationship between sperm DNA integrity and non-return rate (NRR) among Norwegian cross-bred rams, semen from 15 individuals was examined by flow cytometry. Sperm Chromatin Structure Assay (SCSA) quantifies the proportion of spermatozoa with denatured DNA after in situ acid treatment, and the four parameters % DFI, % HDS, MEAN DFI and SD DFI are all different measures of DNA denaturation and maturation. Field fertility, reported as NRR 25 days after insemination was based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Recently, Nordstoga et al [23] showed an association between sperm DNA integrity and the non returned rate among Norwegian cross-bred rams. In this sense, future works must be directed to assess if changes observed in DFI values of rams with alternative genotypes of the G/C −660 mutation at the HSP90AA1 gene promoter have effect on their fertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Nordstoga et al [23] showed an association between sperm DNA integrity and the non returned rate among Norwegian cross-bred rams. In this sense, future works must be directed to assess if changes observed in DFI values of rams with alternative genotypes of the G/C −660 mutation at the HSP90AA1 gene promoter have effect on their fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Thresholds for sub fertility were much lower for boars (6%) and bulls (14.2%) than that for humans (30%). Recently, in rams Nordstoga et al [23] showed an association between sperm DNA integrity and the non returned rate in Norwegian cross-bred rams.…”
Section: Introductionmentioning
confidence: 99%
“…This rapid test has the advantage of being easy to perform, inexpensive from an economic perspective and predictive of sperm fertilizing capacity . Nonetheless, other predictive criteria of sperm fertility are currently being investigated (Nordstoga et al, 2013;Vicente-Fiel et al, 2014). Using reproduction data from many French sheep breeds, the present study aimed to reassess the relationship between mass sperm motility and male fertility.…”
Section: Introductionmentioning
confidence: 98%
“…In the present study, SCSA assay was reliable for distinguishing different qualities of DNA in the sperm cells. This assay has long been considered valuable for measuring DNA quality and its relationship to fertility has been reported for many species (Evenson et al, 1980;Ballachey et al, 1987;Evenson et al, 1994;Sailer et al, 1996;Love and Kenney, 1998;Larson et al, 2000;Januskauskas et al, 2001;Januskauskas et al, 2003;Waterhouse et al, 2006;Morrell et al, 2008;Didion et al, 2009;Nordstoga et al, 2013;Oleszczuk et al, 2013). Therefore, it was used in the present study as a reference assay to which the other assays could be compared.…”
Section: Discussionmentioning
confidence: 97%